COMPUTER HARDWARE RECOGNITION APPLICATION WITH AUGMENTED REALITY TECHNOLOGY - Repiliya Repiliya; Zaid Romegar Mair (UIN Ar-Raniry, 2021)
In the highly development of technology, thus encouraged to human activity facilitation. One of them was education that required technology in applying the learning system to be effective and flexible. Augmented Reality (AR) was a concept of combining virtual and work reality. Augmented Reality could provide advantages in the interaction between humans and computers, it could be a solution in applying teaching and learning process application in computer majors education, it would be interactive by using 3D.In the 3D object was generated into the the real image so visualization was looked like the original object. The strengthness of this application that the object could rotated so it was looked clearly from any side. This application gave many benefits for the users to know and use the hardware computer in clearly and understandable.